2016
DOI: 10.1080/17425255.2016.1244264
|View full text |Cite
|
Sign up to set email alerts
|

The role of fulvestrant in endometrial cancer

Abstract: Endometrial cancer is the most common malignancy of the female genital tract in industrialized countries. The traditional treatment of endometrial cancer is based on a surgical approach. In recent years, systemic endocrine therapy has demonstrated good efficacy in recurrent or metastatic setting, delaying progression, ameliorating quality of life and palliating symptoms. Areas covered: Phase I and II studies on selective estrogen receptor down-regulators used for the treatment of endometrial cancer treatment h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In subsequent studies, the SERM Ospemifene has been shown as an effective in treatment of vaginal symptoms in postmenopausal women (Archer et al 2019) and only acts as an agonist in endometrium in high doses. The SERD fulvestrant/faslodex (Table 2) has been investigated as a treatment for endometrial cancer in phase I/II trials, although well-tolerated, it has low oral bioavailability and further trials are needed (Bogliolo et al 2017). Another recent study suggested dual targeting of ERα with tamoxifen and ERRα with XCT790 may be beneficial for EC treatment, but this requires further validation (Mao et al 2019).…”
Section: Targeting Oestrogen Receptors In Endometrial Disordersmentioning
confidence: 99%
“…In subsequent studies, the SERM Ospemifene has been shown as an effective in treatment of vaginal symptoms in postmenopausal women (Archer et al 2019) and only acts as an agonist in endometrium in high doses. The SERD fulvestrant/faslodex (Table 2) has been investigated as a treatment for endometrial cancer in phase I/II trials, although well-tolerated, it has low oral bioavailability and further trials are needed (Bogliolo et al 2017). Another recent study suggested dual targeting of ERα with tamoxifen and ERRα with XCT790 may be beneficial for EC treatment, but this requires further validation (Mao et al 2019).…”
Section: Targeting Oestrogen Receptors In Endometrial Disordersmentioning
confidence: 99%
“…Only recently has concern arisen that tamoxifen might also increase the risk of ovarian cancer, as it promotes lesions in the fallopian tubes and ovaries (Chene et al, 2014). Novel SERMs have been developed to combat estrogen-dependent cancers, including toremifene and raloxifene, together with the selective ER down-regulators, such as selective receptor downregulator fulvestrant (for reviews, see Bogliolo et al, 2017; Traboulsi et al, 2017). Further clinical studies on patients with endometrial and ovarian cancer are currently awaited.…”
Section: Pharmacological Interventions That Target Intracrine Actionsmentioning
confidence: 99%
“…Currently the only FDA approved SERD is fulvestrant, originally indicated for breast cancer progressing after tamoxifen or aromatase inhibitor (AI) treatment, but recently approved for first line endocrine therapy [ 1 – 4 ]. While fulvestrant has proven clinically effective with manageable adverse side effects, the drug is well known for its poor bioavailability [ 5 ]. It can only be administered as a monthly intramuscular injection and is believed to have limited drug exposure and ER turn-over in patients [ 6 7 ].…”
Section: Introductionmentioning
confidence: 99%